Optimization of PLA foams produced by supercritical method: influence of chemical modification and incorporation of CNC on the resulting cellular structures - Suquisaqui, Ana Beatriz Valim (2024)
The main objective of this research was to study the influence of chemical modification and the introduction of cellulose nanocrystals (CNC) on the properties of PLA, with a view to producing foams using supercritical CO2 as a foaming agent. In parallel, to produce a cellulose-based porous material, a CNF cryogel was produced with an increased hydrophobic character, without the need for chemical treatments. For the chemical modification of PLA, GMA was used as a modifying agent, in the presence of peroxide as an initiator. For the strategy of incorporating fillers, the CNC was chemically modified by mechanochemistry using octadecyl isocyanate to increase compatibility with the PLA matrix. The nanocomposites were produced in different concentrations of neat and modified CNC. The cellulose-based cryogels were produced by freeze-drying a suspension of CNF with PLA nanoparticles which, after being freeze-dried, were subjected to thermal treatment. The results showed that the chemical modification of PLA resulted in significant changes in the cell structures of the foams, in which an optimum concentration between reagents resulted in homogeneous cells in the order of 15 μm. The introduction of CNC was more significant at 10 wt%, which neat CNC at this concentration resulted in the smallest cell size and highest expansion ratio. As for the CNF cryogel, the introduction of 10 wt% PLA nanoparticles followed by heat treatment proved to be efficient in increasing the material hydrophobic character, without impacting the internal structure of the pores. In this way, the results obtained in this doctoral thesis can support further research into the development or improvement of foamed and/or porous materials based on polymers from renewable sources.